Effect of culture parameters on the production of the edible mushroom Grifola frondosa (maitake) in tropical weathers - Barreto, Sandra Montoya (2008)
Hitherto, little effort has been directed to improve culture conditions for commercial development of maitake (Grifola frondosa), an edible and medicinal fungus, due to the short history of cultivation, particularly in tropical weathers. The purpose of this research was analyzing the environmental factors required for successful basidiome development on synthetic substrates in Colombia. We evaluated different cereal grains (corn, barley, sorghum and rice) for spawn production; and industrial by-products (such as coffee spent-ground and oak-sawdust) as substrates for mushroom production. Exploiting these residues for G. frondosa solid culturing would primarily provide edible mushroom and simultaneously help in resolving their disposal problem. The use of corn grains as substrate for spawn production results an important factor for reducing crop cycle time. A cold shock to 10°C was requisite for basidiome formation. Coffee spent-ground was a good substrate for mycelial growth, but not for mushroom production. When using oak sawdust plus corn bran as substrate, we obtained consistent yields with combined high biological efficiency (BE) (35.3%), best quality mushrooms, and a crop cycle of 12-14 weeks. The results achieved in this investigation contribute to expand the knowledge on this fungus, and compare favorably with previous works in the northern hemisphere with respect to BE, mushroom quality and crop cycle time.